Cormorant predation mortality of perch (Perca fluviatilis) in coastal and archipelago areas, northern Baltic Sea - Heikinheimo, Outi; Marjomäki, Timo J; Olin, Mikko; Rusanen, Pekka (Oxford University Press, 2021)
Perch (Perca fluviatilis) is an important prey species of the great cormorant (Phalacrocorax carbo sinensis) in the coastal waters of the northern Baltic Sea. The annual predation mortality caused by cormorants was estimated based on the consumed numbers of perch in relation to the abundance of perch in vulnerable age groups in the sea. We used existing stock assessment data (Archipelago Sea) or a simple population model in other areas (Gulf of Finland, Bothnian Sea, and Quark), based on commercial and recreational perch catches, and estimated fishing and natural mortalities, with distributions describing our understanding about the likelihood of different values for every variable. The median predation mortality was 4–10% annually, depending on the sea area. The area-specific 80% likelihood limits ranged from 3 to 21% annually. Compared to a recent perch tagging study in the Quark, the cormorant-induced mortality estimates were considerably lower, but the likelihood distributions partly overlapped. The results were sensitive to the estimated number of vulnerable perch in the population, which in turn largely depends on the natural mortality in young perch age groups.
Keywords: Baltic Sea; coastal fisheries; cormorant; mortality; perch; predation